Penyuluhan terapi pijat wajah untuk mengatasi gerakan tutup mulut pada balita - Marice Marice; Therecia Wijayati; Youlenta Ernesonta; Intan Intan; Elsa Elsa; Cristianingsih Sri Paninggih (JOURNAL of Public Health Concerns, 2026)
Background: The behavior of keeping the mouth closed (refusing food) in toddlers is an issue that can affect feeding, communication, and the development of oromotor function. One non-pharmacological intervention involves educating parents on facial massage techniques to stimulate facial muscles and help improve oral movement function. Purpose: To enhance parents' knowledge and skills in performing facial massage to help address the issue of toddlers keeping their mouths closed (refusing food). Method: This activity was conducted on February 24, 2026, at the Pal III Community Health Center (Puskesmas) in Sungai Jawi Urban Village, Pontianak City District, West Kalimantan. The study involved 77 mothers of toddlers as respondents. The initiative aimed to empower mothers through education on complementary care specifically facial massage to address this refusal behavior. Respondents' knowledge and understanding were assessed using a one-group pretest-posttest design, with questionnaires administered before and after the educational session. Skill levels were evaluated through observation of practical simulations using anatomical models (phantoms). Evaluation involved analyzing the aggregated questionnaire data and descriptively reporting the results regarding the achievement and improvement of respondents' knowledge concerning the benefits of facial massage for this issue. Results: The study showed that the mean age of respondents was 32.3 years, with the majority (50.6%) falling within the 20–29 age range. Evaluation results indicated an increase in participants' knowledge regarding the benefits of facial massage for toddlers experiencing "refusal to eat" behavior (characterized by the child closing their mouth tightly); knowledge levels rose from 27.3% prior to the educational activity to 79.2% afterward. Participants were also able to correctly demonstrate the facial massage techniques following the demonstration and guided practice sessions. Conclusion: The educational program on facial massage to address refusal-to-eat behavior in toddlers was successfully implemented and received a positive response from participants; it effectively raised awareness regarding the causes of this behavior and its impact on the nutritional balance required for optimal toddler growth and development. Combining educational leaflets with anatomical models (phantoms) proved to be an effective strategy for conveying information and teaching participants how to perform facial massage safely and correctly. Suggestion: It is recommended that healthcare professionals conduct periodic educational sessions on facial massage for toddlers and involve community health volunteers. This approach ensures the continuity of information and knowledge sharing, thereby supporting family health and fostering optimal growth and development in toddlers. Keywords: Facial massage; Health education; Refusal to eat; Therapy; Toddlers Pendahuluan: Gerakan tutup mulut pada balita merupakan salah satu permasalahan yang dapat memengaruhi proses makan, komunikasi, dan perkembangan fungsi oromotor. Salah satu upaya nonfarmakologis yang dapat dilakukan adalah penyuluhan kepada orang tua mengenai teknik pijat wajah sebagai stimulasi otot-otot wajah untuk membantu meningkatkan fungsi gerakan mulut. Tujuan: Untuk meningkatkan pengetahuan dan keterampilan orang tua dalam melakukan pijat wajah wajah guna membantu mengatasi gerakan tutup mulut pada balita. Metode: Kegiatan ini dilaksanakan pada tanggal 24 Februari 2026 di Puskesmas Pal III Kelurahan Sungai Jawi, Kecamatan Pontianak Kota, Kalimantan Barat. Melibatkan 77 ibu yang memiliki balita untuk menjadi responden. Sasaran kegiatan ini adalah pemberdayaan ibu melalui edukasi asuhan komplementer pijat wajah balita dalam mengatasi GTM pada balita. Pengukuran tingkat pengetahuan dan pemahaman responden dilakukan dengan pendekatan one group pretest and posttest design menggunakan kuesioner yang diberikan sebelum (pretest) dan sesudah kegiatan edukasi (posttest). Untuk tingkat kemampuan responden di evaluasi berdasarkan observasi dari simulasi ketika melakukan praktik pemijatan wajah dengan menggunakan phantom. Evaluasi kegiatan dilakukan dengan mengkaji hasil akumulasi kuesioner dan disampaikan secara deskriptif terkait pencapaian dan peningkatan pengetahuan responden tentang manfaat pemijatan wajah terhadap GTM pada balita. Hasil: Menunjukkan bahwa usia rata-rata responden adalah 32.3 tahun dan mayoritas berada direntang usia 20-29 tahun yaitu sebesar 50.6%. Berdasarkan hasil evaluasi menunjukkan bahwa tingkat pengetahuan peserta tentang manfaat pijat wajah pada balita dapat menurunkan GTM mengalami peningkatan dari sebelum kegiatan edukasi sebesar 27.3% menjadi sebesar 79.2% setelah kegiatan edukasi. Peserta juga mampu mempraktikkan teknik pijat wajah sesuai prosedur dengan baik dan benar setelah mengikuti demonstrasi dan pendampingan. Simpulan: Kegiatan penyuluhan pijat wajah untuk mengatasi gerakan tutup mulut (GTM) pada balita telah terlaksana dengan baik dan mendapat respons positif dari para peserta secara efektif menumbuhkan kesadaran dalam mengantisipasi penyebab GTM dan dampaknya terkait keseimbangan gizi untuk tumbuh kembang balita. Perpaduan media edukasi antara leaflet dan phantom sebagai alat peraga merupakan strategi efektif dalam penyampaian informasi dan ketrampilan peserta dalam melakukan pijat wajah secara benar dan aman. Saran: Diharapkan untuk tenaga kesehatan dapat melakukan kegiatan edukasi pijat wajah balita secara berkala dan melibatkan kader sehingga informasi dan nilai pengetahuan dapat berkembang berkelanjutan sebagai upaya dukungan terhadap kesehatan keluarga dengan balita yang memiliki tumbuh kembang optimal.